Proliferation rate and expression of stem cells markers during expansion in primary culture of pulp cells - Turrioni, Ana Paula (2021)
The aim of the present study was to evaluate the proliferation rate and the expression of stem cells markers during expansion in primary culture of dental pulp stem cells (DPSCs), comparing different techniques (explant and enzymatic digestion), subject ages (up to 40 and over 40) and cell passages (#2, #5 and #8). DPSCs were isolated using either the enzymatic digestion (ED) or explant (EX) technique. The number of days needed for the cells to reach confluence was determined. Immunophenotyping was performed by immunofluorescence and flow cytometry analysis using antibodies specific for nestin, vimentin, CD44, CD146, Oct3/4 and CD34. Data were subjected to three-way analysis of variance (n = 6/group). The ANOVA tests were complemented by Tukey’s or t-tests (p < 0.05). The variables “donor age” and “technique” were analyzed to define the optimal desirability value using a response optimization. DPSCs presented a high proliferation rate from passages 2 to 5 while cells from passage 8 proliferated at a slower rate. For all markers, no significant difference was observed among passages, irrespective of the technique used or the donor’s age. The mean fraction of specific antibodies was 73.7% (± 11.5), 49.0% (± 18.7), 80.1% (± 8.0), 45.2% (± 13.7), 64.7% (± 5.3) and 2.0% (± 1.5) for CD44, OCT, vimentin, nestin, CD146 and CD34, respectively. The highest optimal desirability value was obtained using the ED technique and cells from younger patients (d = 0.92). However, it was concluded that neither the isolation technique nor the donor age or cell passage significantly interfered with the stem cell phenotype and proliferation rate during cell expansion.